Bridging the Language Gap: An ESP Needs Analysis for Batik Sellers at Beringharjo Market - Rustananda, Dani; Kusumawardana, Kwica Guswantoro; Suharyanto, S; Haryanti, Dwi (Universitas Muhammadiyah Surakarta, 2024)
Purpose: This study aims to explore the significance of English language proficiency among batik sellers in Beringharjo Market, Yogyakarta, in response to the rise of international tourism. It focuses on identifying specific English language needs that support effective communication with foreign tourists in daily business transactions. Methodology: This qualitative research involved four batik sellers as participants. Data were gathered through in-depth interviews to gain insights into their experiences, language use, and perceptions regarding the importance of English in their business activities. Results: The findings revealed varying perspectives among participants. Some sellers viewed English as essential to customer engagement, while others considered it less critical. The participants also demonstrated diverse levels of English proficiency, with speaking and listening as the most utilized skills. Common challenges included pronunciation difficulties and limited vocabulary. Applications/Originality/Value: This research offers practical insights for designing English for Specific Purposes (ESP) programs tailored to traditional market vendors. By aligning language training with real communicative needs, particularly in high-tourism areas, such initiatives can empower small business owners to interact confidently with international customers and enhance the competitiveness of local cultural economies.